Linguistic behaviors by Central Valley in habitants towards the Spanish linguistic variation of Guanacaste - Sancho Ugalde, María (2025)
Introduction. This paper analyzes the linguistic behaviors present in a sampleof Central Valley students, or vallecentraleños, from the National University of Costa Rica —Regional Chorotega Campus and Omar Dengo Campus —towards the linguistic variation of Spanish spoken in Guanacaste. Objective. Analyze the linguistic behaviors in a sample of students from the Central Valley from the National University of Costa Rica towards the linguistic variation of Spanish spoken in Guanacaste. Methodology. In order to accomplish the previously defined objective, a five-point Likert-type questionnaire is used as data collection instrument. Afterwards, this data is analyzed through figures and three openquestions. This qualitative approach is used as valuable information to complement the statistical data. Results. The vallecentraleños interviewed (natives and migrants) admit to being aware of these linguistic variation between these two Spanish variants from Guanacaste and Central Valley. Regarding this linguistic variation under study, the following is observed in Spanish spoken in Guanacaste: linguistic prejudice, linguistic accommodation or adaptation processes, linguistic insecurity, linguistic modifications, linguistic loyalty and identity reinforced with more conscious and inclusive attitudes towards Costa Rican linguistic and cultural diversity. Conclusions. We can conclude that the separation that has existed throughout history between the linguistic variations of Guanacaste and Central Valley Spanish is still preserved. Nevertheless, this analysis of linguistic behaviors shows a leveling and gradual approximation of these two linguistic variations. This is evident in the positive attitudes of respect and linguistic identity manifested by the students interviewed, particularly those who have experienced migration. To guide the reader, this paper is organized into five sections: background, theoretical framework, methodology, results of the quantitative and qualitative analysis of linguistic behaviors of the locations under study, and conclusions.